J. QUETGLAS - Breviario de Ronchamp - Pierini, Orsina Simona (ZARCH, 2018)
Josep QuetglasBreviario de RonchampEdiciones Asimétricas, Madrid, 2017, 275 pp., 243 ilustracionesIdioma: español. ISBN 978-84-946957-9-7